Gastropod Communities in Seagrass Ecosystems in Tafaga Coastal Waters and Figures, Moti Island District, Ternate City - Sunarti, Sunarti; Abubakar, Yuyun; Abubakar, Salim; Subur, Riyadi; Rina, Rina; Abdul Kadir, Masykhur; Susanto, Adi Noman; H. Fadel, Ariyati (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
This study was conducted with the aim of knowing the composition of gastropod species that live in the seagrass area of Tafaga and Figur coastal waters, Moti Island and to determine the structure of the gastropod community which includes density, diversity, dominance and species evenness. The sampling technique was carried out using the 50x50 m block area method. The composition of gastropod species found in coastal waters of Tafaga (station 1) was 6 species and coastal waters of Figure (station 2) were 17 species. The highest density of gastropod species in station 1 was found in the Nassarius pullus species and the lowest in the Naria erosa species. Meanwhile, in the station 2, the highest density of gastropod species was also found in the Nassarius pullus species and the lowest in the Strombus lentiginosus species. The diversity of gastropod species at station 1 is low and there are species that dominate and the distribution of species is quite even. While at station 2 the species diversity is moderate and no species dominates and the species distribution is evenly distributed.